2019
DOI: 10.3233/aac-190457
|View full text |Cite
|
Sign up to set email alerts
|

On the expressive power of collective attacks

Abstract: In this paper, we consider argumentation frameworks with sets of attacking arguments (SETAFs) due to Nielsen and Parsons, an extension of Dung's abstract argumentation frameworks that allow for collective attacks. We first provide a comprehensive analysis of the expressiveness of SETAFs under conflict-free, naive, stable, complete, admissible, preferred, semi-stable, and stage semantics. Our analysis shows that SETAFs are strictly more expressive than Dung AFs. Towards a uniform characterization of SETAFs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…Recent work [16] has shown that this is indeed the case, under the important assumption that the set of arguments is fixed. In other words, [16] showed that, given a set of arguments, one can create a SETAF whose semantics cannot be captured by any AAF (using the same set of arguments).…”
Section: Generated Argumentation Frameworkmentioning
confidence: 89%
See 3 more Smart Citations
“…Recent work [16] has shown that this is indeed the case, under the important assumption that the set of arguments is fixed. In other words, [16] showed that, given a set of arguments, one can create a SETAF whose semantics cannot be captured by any AAF (using the same set of arguments).…”
Section: Generated Argumentation Frameworkmentioning
confidence: 89%
“…• We show how a SETAF can be modelled as an AAF, with an exponential increase in the number of arguments considered, and how the extensions of the two frameworks relate to each other (Section 6). Our approach circumvents the limitation formally proven in [16], where it was shown that SETAFs are strictly more expressive than AAFs when considering a fixed set of arguments.…”
Section: Contributions and Paper Summarymentioning
confidence: 93%
See 2 more Smart Citations
“…Secondly, since other generalizations of Dung AFs can be seen as special case of ADFs, results on ADFs carry over to these special cases. We exemplify this aspect in the paper, by deriving new results for argumentation frameworks with collective attacks (SETAFs) [27] which have received increasing interest recently [18,21]. To the best of our knowledge concepts like symmetric SETAFs have not been investigated yet, and we provide first results in this direction.…”
Section: Introductionmentioning
confidence: 93%